Classifying news versus opinions in newspapers: Linguistic features for domain independence. (21st February 2017) - KRÜGER, K. R.; LUKOWIAK, A.; SONNTAG, J.; WARZECHA, S.; STEDE, M.
Abstract: Newspaper text can be broadly divided in the classes 'opinion' (editorials, commentary, letters to the editor) and 'neutral' (reports). We describe a classification system for performing this separation, which uses a set of linguistically motivated features. Working with various English newspaper corpora, we demonstrate that it significantly outperforms bag-of-lemma and PoS-tag models. We conclude that the linguistic features constitute the best method for achieving robustness against change of newspaper or domain.